Community Development through Supply Chain Strategy: Governance of Village Enterprise - Yohanes Yakobus Werang Kean; Intiyas Utami; Aprina Nugrahesty Sulistyo Hapsari (International Journal of Supply Chain Management, 2020)
Abstract— Managing the supply chain has become a way of improving competitiveness by reducing uncertainty and improving service. This paper will seek to highlight the importance of managing the Supply Chain and logistics in Indonesia rural markets to delivers goods and services in a cost effective manner. The village enterprise has become the Indonesian government's program to develop the economy of villages through the supply chain. The management of village enterprise in traditional villages encounters two situations. On the one hand, the village enterprise is required to have good governance, while on the other hand it deals with the conditions of supply chain strategy. The mutual influence between supply chain and communities offers opportunities to integrate sustainability initiatives into the chain. So the objective of this research is to explore the understanding of stakeholders about the supply chain of enterprise at the village of Wologai. This research also explores the supply chain that supports the governance of village enterprises. Village of Wologai as a traditional village, it has high supply chain strategy, for example, there is a traditional leader i.e. “musalaki” who is a respected figure in the village community. Supply chain strategy that has the potential to hamper governance implementation, among others, is in terms of meeting the demands of indigenous peoples who want enterprise activities to prioritize culture ceremonies rather than discipline in preparing good governance.